Victimology in the 21st Century: A Global Examination of Victimization, Support Systems, and Public Perception - Manuel, Erwin Miguel; Badar, Dominador; Sisgon, Girlie; Ebuen, Robin Jay (International Journal of Sustainability and Advanced Integrated Research, 2026)
This scoping review examines the evolving field of victimology in the 21st century, emphasizing the global variations in victim perception, support systems, and the impact of technology. The review is driven by three main objectives: to explore the cultural dimensions of victimhood and public perception across different global settings; to assess the barriers to effective victim support in resource-poor environments; and to analyze the dual role of technology as both a driver of victimization and a tool for recovery. This research is aligned with the United Nations Sustainable Development Goal 5, which aims to eliminate violence against women, and Goal 16, which focuses on ensuring equal access to justice for all. By reviewing recent literature, the study reveals that "victimization" is often deeply influenced by cultural factors, with societal norms shaping the legitimacy of harm. In countries with limited resources, Western support models often fail due to a lack of local adaptation and infrastructure. Additionally, the growing prevalence of digital technologies has led to the emergence of "cyber-victimology," where technology-facilitated abuse is widespread, yet survivors are frequently blamed for not adequately protecting themselves online. The findings suggest that achieving global justice necessitates a shift toward "cultural victimology" and the incorporation of local perspectives in policy-making. By focusing on context-appropriate interventions and challenging rigid "ideal victim" stereotypes, the international community can more effectively address the goals set out in the 2030 Agenda for Sustainable Development.